Implikasi Agreement on Agriculture (Aoa/Wto) Terhadap Pengaturan Perdagangan Produk Pertanian Indonesia - Sri Asih Roza Nova (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The aim of this scientific writing is to find out the legal implications of the AoA/WTO for trade in the Indonesian agricultural sector, as well as to find out how Indonesia provides legal protection for trade in agricultural products due to the liberalization of world trade. This scientific research uses normative juridical research methods, and the data collected will be analyzed juridically qualitatively, then the results of this research will be described descriptively analytically. From the research results, the author obtained data that to implement the AoA/WTO provisions, Indonesia updated its legal provisions in the agricultural sector through several national provisions. However, this implementation has implications that have a negative impact on farmers, as a result trade in the Indonesian agricultural sector decreases, such as imports of food products increasing, farmers' income decreasing, there are no subsidies for farmers, food insecurity and hunger, Bulog becomes a company, and etc. To anticipate the negative impact of trade liberalization on the agricultural sector, the Indonesian government has made such efforts, such as enacting Law No. 29 of 2000, concerning the protection of plant varieties, Presidential Decree No. 77 of 2005, concerning the procurement and distribution of subsidized fertilizers, at the beginning of September 2007, The Decree of the Coordinating Minister for the Economy gave full authority to Bulog, in May 2007, the government issued a Draft Government Regulation (RPP) concerning the National Agrarian Reform Program (PPAN) / Landreform, and at the international level, Indonesia created the SP (Special Product) and SSM (Special Product) programs. Safeguard Mechanism) which is still being fought for in the WTO forum to get its ratification.